Fixed ammonium in some Finnish soils - Armi Kaila (Agricultural and Food Science, 1966)
The nonexchangeable or fixed NH4-N was determined by the method of SCHACHTSCHABEL in 130 samples of Finnish mineral soils. In this relatively heterogeneous material consisting of 44 samples from the surface layer down to 20 cm and 86 samples from the deeper layers, the pH values ranged from 3.3 to 7.5, the contents of clay from 0 to 96 per cent, organic C from 0.03 to 6.6 per cent, and Kjeldahl-N from 0.13 to 4.53 mg/g. In the 46 finesand, loam and silt soil samples, the content of nonexchangeable NH4-N was, on the average, 90 ± 30 ppm ranging from 0 to 190 ppm. In the 84 clay soil samples it ranged from 40 to 620 ppm, with an average of 290 ± 30 ppm. The heavy clay soils of the deeper layers were particularly rich in fixed NH4-N containing it averagely 400 ± 40 ppm. Because of these soils the mean value in the samples of the deeper layers was as high as 260 ± 30 ppm and thus significantly higher than the corresponding figure in the surface soils, 140 ± 40 ppm. In the clay soils the amount of nonexchangeable ammonium was correlated with the clay fraction less than 0.6 μ (r = 0.74***), but not at all with the coarser clay. In the finesand, loam, and silt soils no correlation between the contents of fixed ammonium and clay was detected. No close relationship existed between the indigenous fixed ammonium and the capacity of the soil to fix applied ammonium. If the sum of these quantities would represent the total ammonium fixing capacity of the soil, about one half of this capacity would be saturated by the native fixed ammonium in the topsoil. In the subsoils the rate of saturation would be much lower. In the topsoil samples the amount of nonexchangeable NH4-N corresponded in the non-clay soils to 4 ± 2 per cent and in the clay soils to 9 ± 3 per cent of the Kjeldahl-N. In the subsoil samples the corresponding average percentage was 52 ± 5. The rather low ratios of organic C to Kjeldahl-N in the clay soils of the deeper layers may be taken to indicate that a part of the Kjeldahl-N was not in organic compounds. The C/N-ratios obtained when the amount of nonexchangeable NH4-N is subtracted from the Kjeldahl-N may be too high to characterize the soil organic matter, since it is likely that all the fixed NH4-N was not determined by the Kjeldahl-procedure.